Harnessing Solar Energy And Sustainable Water Practices In India: A Pathway To Environmental Resilience (International Journal of Environmental Sciences, 2025)
The global transition to sustainable energy is at a critical juncture, spurred by increasing energy needs from expanding population and industrialization. In contrast, traditional energy resources have previously powered economic growth; their degradation of the environment and limited nature point towards switching to cleaner energy options. Renewable energy, solar, wind, and hydroelectric, in particular, provide a promising alternative, although these come with drawbacks like intermittency, cost of infrastructure, and technological constraints. Governments are increasingly making renewable energy more cost-competitive and economically viable by using targeted policy tools such as carbon pricing schemes, subsidies, and tax incentives. This report looks at the larger picture of renewable energy uptake. It presents in-depth case studies of two pioneering solar projects in India: the REWA Solar Park in Madhya Pradesh and the GED- COL Solar PV Project in Odisha. REWA, India's largest 750 MW solar park, exemplifies effective public-private partnership, creative financing, and mass-scale economic and environmental benefits, such as a sizeable reduction in CO emissions and energy expenses. GEDCOL, a 10 MW solar power plant, prioritizes rural electrification, sustainable development, and community-centric planning in Odisha. Both examples illustrate how strategic planning, strong policy frameworks, and stakeholder consultations can be used to catalyze meaningful renewable energy deployment. These case studies provide replicable models for developing countries balancing economic growth with ecological sustainability.